Introduction to laser technology - Hitz, C. Breck; Ewing, J. J. (James J.), 1942-; Hecht, Jeff. (Hoboken : John Wiley & Sons, 2012)
520 The only introductory text on the market today that explains the underlying physics and engineering applicable to all lasersAlthough lasers are becoming increasingly important in our high-tech environment, many of the technicians and engineers who install, operate, and maintain them have had little, if any, formal training in the field of electro-optics. This can result in less efficient usage of these important tools. Introduction to Laser Technology, Fourth Edition provides readers with a good understanding of what a laser is and what it can and cannot do. The book explains what types of laser to use for different purposes and how a laser can be modified to improve its performance in a given application. With a unique combination of clarity and technical depth, the book explains the characteristics and important applications of commercial lasers worldwide and discusses light and optics, the fundamental elements of lasers, and laser modification.
16. Fiber Lasers -- Acceptance Angle and Numerical Aperture -- Doping Optical Fibers -- Pumping Fiber Lasers -- Fabricating Optical Fibers -- Feedback for Fiber Lasers -- High Power Fiber Lasers -- Large-Mode-Area Fibers -- Holey Fibers -- 17. Gas Lasers: Helium-Neon and Ion -- Gas-Laser Transitions -- Gas-Laser Media and Tubes -- Laser Excitation -- Optical Characteristics -- Wavelengths and Spectral Width -- He-Ne Lasers -- Principles of He-Ne Lasers -- Structure of He-Ne Lasers -- Ar-and Kr-Ion Lasers -- 18. Carbon Dioxide and Other Vibrational Lasers -- Vibrational Transitions -- Excitation -- Types of CO2 Lasers -- Optics for CO2 Lasers -- Chemical Lasers -- 19 Excimer Lasers -- Excimer Molecules -- Electrical Considerations -- Handling the Gases -- Applications of Excimer Lasers -- 20 Tunable and Ultrafast Lasers -- Dye Lasers -- Tunable Solid-State Lasers -- Nonlinear Converters -- Ultrafast Lasers -- Glossary -- Further Reading -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Lasers; TECHNOLOGY & ENGINEERING -- Electrical; Electrical engineering; Engineering; TECHNOLOGY & ENGINEERING -- Lasers & Photonics; Lasers; Electronic books